Nordic elites in transformation, c. 1050-1250. (New York, NY)
1 online resource.
Keywords: Nordic Elites in Transformation, c. 1050-1250, Volume II explores the structures and workings of social networks within the elites of medieval Scandinavia to reveal the intricate relationship between power and status. Section one of this volume categorizes basic types of personal bonds, both vertical and horizontal, while section two charts patterns of local, regional and transnational elite networks from wide-scope, longitudinal perspectives. Finally, the third section turns to case-studies of networks in action, analyzing strategies and transactions implied by uses of social resources in specific micro-political settings. A concludingchapter discusses how social power in the North compared to wider European experiences. A wide range of sources and methodologiesis applied to reveal how networks were established, maintained, and put to use - and how they transformed in processes of centralizing power and formalizing hierarchies. The engagement with and analysis of intriguing primary source material has produced a key teaching tool for instructors and essential reading for students interested in the workings of medieval Scandinavia, elite class structures, and Social and Political History more generally.